2013
DOI: 10.7448/ias.16.1.17998
|View full text |Cite
|
Sign up to set email alerts
|

A survey of paediatric HIV programmatic and clinical management practices in Asia and sub‐Saharan Africa—the International epidemiologic Databases to Evaluate AIDS (IeDEA)

Abstract: IntroductionThere are limited data on paediatric HIV care and treatment programmes in low-resource settings.MethodsA standardized survey was completed by International epidemiologic Databases to Evaluate AIDS paediatric cohort sites in the regions of Asia-Pacific (AP), Central Africa (CA), East Africa (EA), Southern Africa (SA) and West Africa (WA) to understand operational resource availability and paediatric management practices. Data were collected through January 2010 using a secure, web-based software pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 12 publications
(13 reference statements)
1
23
0
Order By: Relevance
“…In contrast, for children the chance of VL suppression did not differ across regions which may indicate less between-region heterogeneity and less variations in both patient-level and site-specific factors. High clinical resources and access to paediatric antiretroviral formulations were reported in a survey of paediatric HIV programmatic and clinical management practices in Asia and sub-Saharan Africa 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, for children the chance of VL suppression did not differ across regions which may indicate less between-region heterogeneity and less variations in both patient-level and site-specific factors. High clinical resources and access to paediatric antiretroviral formulations were reported in a survey of paediatric HIV programmatic and clinical management practices in Asia and sub-Saharan Africa 24 .…”
Section: Discussionmentioning
confidence: 99%
“…These sites are predominantly public or university-based pediatric HIV referral clinics. A 2010 survey of ten TApHOD sites found that only 30% provide food supplementation for malnourished patients, 13 however, nutritional aid (milk/formula, rice, or cash) is usually provided to children in need through local governments in the region. The same survey also indicated that 90% of sites provide nutritional counselling to patients and their caregivers, 80% provide micronutrients for patients, and 60% routinely initiate cotrimoxazole prophylaxis in HIV-exposed infants (unpublished results).…”
Section: Methodsmentioning
confidence: 99%
“…The seven regions included in IeDEA are North America, Caribbean/Central and South America, Asia/Pacific, and four regions in sub-Saharan Africa (East Africa, West Africa, Central Africa and Southern Africa). 6,10-14 For the present analysis we included data from the African and Asia/Pacific regions of IeDEA. In addition, we included North American and Latin American data from the NICHD International Site Development Initiative (NISDI), 15 the Pediatric HIV/AIDS Cohort Study (PHACS), 16 and the International Maternal Pediatric Adolescent AIDS Clinical Trials (IMPAACT) 219C study.…”
Section: Methodsmentioning
confidence: 99%